EVALUATING BANK PERFORMANCE THROUGH FINANCIAL INDICATORS - Abdullayev Xursandbek Uktam ugli (Modern American Journals, 2025)
This article examines the theoretical and practical foundations of assessing bank performance through key financial indicators. Financial metrics such as liquidity, profitability, asset quality, and capital adequacy are essential for determining the resilience, stability, and efficiency of banking institutions. The study also reflects on Uzbekistan’s recent banking sector developments, offering international comparisons and scholarly insights.
Keywords: Financial performance, banks, liquidity, profitability, ROA, ROE, capital adequacy, banking supervision, risk management.